Is periodontal infection a risk factor for thromboembolic disease? A systematic review - Oinam Monica Devi; Jyoti Gupta; Gurparkash Singh Chahal; Ashish Jain (Wolters Kluwer Medknow Publications, 2023)
Background: Venous thromboembolism (VTE) is a rising major health problem comprising pulmonary embolism (PE) and deep vein thrombosis. It is of concern due to premature mortality, increased morbidity, and associated healthcare costs and hospitalization. Periodontitis can increase the risk of VTE by way of systemic inflammation induced by infection that can contribute to hypercoagulability and platelet aggregation. This systematic review aims to synthesize all the evidence concerning periodontal infection as a risk factor for thromboembolic disease. Materials and Methods: A search for articles published from 1967 till December 2020 was conducted in the PubMed (MEDLINE), Scopus, and EMBASE data bases. Results: Five hundred and five articles were retrieved after running search strategies in PubMed, Scopus, and EMBASE search databases. Based on the inclusion criteria, three clinical studies, two case series, and ten case reports were included for qualitative analysis. The presence of periodontal disease was reported to influence the occurrence of venous thromboembolic disease with a statistical significance of <0.010. Case series and case reports of septic PE due to periodontal disease showed complete resolution of lung lesions and subsiding of symptoms after dental treatment and antimicrobial therapy. Conclusions: The results of this systematic review suggested for an association between periodontal disease and the incidence of thromboembolic disease. As most of the included/available studies are case series and case reports, the strength of evidence is weak. Evidence generated from well-designed longitudinal controlled clinical trials may be helpful to further assess the strength of the association.